#TITLE_ALTERNATIVE# - PRANOLO (NIM 10104053), FERRY
We will discuss a trigonometric interpolation method using Sine Fourier Series and Cosine Fourier Series. The result will minimize an energy, called energy of potential axial. The result is a linear piecewise function, which is the Sine Fourier Series or Cosine Fourier Series of the linear piecewise function. The method and procedure to find the solution through the interpolation that minimize energy in general (Eα) was researched by H. Gunawan (2007).